GIS based identification of water harvesting potential area in the Bale lowland of south eastern Ethiopia - Chala Chimdessa; Zerihun Dibaba; Gadisse Dula (Geology, Ecology, and Landscapes)
Assessment of potential surface runoff harvesting sites is an important undertaking in a country like Ethiopia, where high spatial variability in rainfall, recurrent drought, and flash floods are common. In this study, a geographical information system (GIS)-based multi-criteria evaluation was used to select potential rainwater harvesting sites in Oromia, the Bale lowland, Ethiopia. The Analytic Hierarchy Process (AHP) was used for standardization of the criteria and weight overlay analysis of multicriteria for a combination of multi-layers using ArcGIS 10.8. Six criteria layers, including slope, runoff, soil depth, precipitation, soil texture, and land use land cover, were derived to identify the rainwater-harvesting catchment. The analysis, shows that of the total 500 km2 of the catchment area 29.18% of the area has highly suitable 40.87% of the area has suitable 22.49% of the total area has moderately suitable 6.98% of the area has marginally suitable and 0.5% of the area is not suitable for runoff water harvesting at the study area. Providing accurate and precise spatial representation of the physiology and land use for the analysis of runoff generation potential sites within the study area is an important step in developing an integrated strategy for surface rainwater harvesting plans in the study area.